2018
DOI: 10.1521/pedi_2017_31_293
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Exclusion on “Reading the Mind in the Eyes” Performance in Relation to Borderline Personality Disorder Features

Abstract: In this study we used the Reading the Mind in the Eyes Test (RMET) to explore facial emotion recognition in borderline personality disorder (BPD). We also used Cyberball, a computerized task designed to mimic social ostracism, to examine the response of BPD-feature participants to social exclusion. Seventeen individuals with BPD features were compared to 16 healthy controls on RMET performance pre- and post-exclusion via Cyberball. Our results revealed a significant interaction between BPD-feature status and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
1
10
0
2
Order By: Relevance
“…Their interpretation bias in social encounters has been conceptualized as a failure of mentalizing with an (over-)attribution of malevolent intentions to others and a lack of discrimination between self and other ( Sharp et al, 2011 ; Domsalla et al, 2014 ; Herpertz and Bertsch, 2014 ). As such, the breakdown of mentalization might induce a vicious circle: Once patients feel ostracized, they may not recognize any agreeable interactional cues by others anymore and perceive neutral mimicry as aversive ( Staebler et al, 2011a ; Savage and Lenzenweger, 2017 ). Feelings of exclusion are therefore perceived in “psychic equivalence” (i.e., an inner reality is perceived as “over”-real, Bateman and Fonagy, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their interpretation bias in social encounters has been conceptualized as a failure of mentalizing with an (over-)attribution of malevolent intentions to others and a lack of discrimination between self and other ( Sharp et al, 2011 ; Domsalla et al, 2014 ; Herpertz and Bertsch, 2014 ). As such, the breakdown of mentalization might induce a vicious circle: Once patients feel ostracized, they may not recognize any agreeable interactional cues by others anymore and perceive neutral mimicry as aversive ( Staebler et al, 2011a ; Savage and Lenzenweger, 2017 ). Feelings of exclusion are therefore perceived in “psychic equivalence” (i.e., an inner reality is perceived as “over”-real, Bateman and Fonagy, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental studies have shown aversive reactions of BPD patients after rejection. For this purpose, most of the previous studies simulated ostracism through the exclusion condition of the Cyberball paradigm with significant emotional and behavioral consequences, including neurobiological investigations ( Ruocco et al, 2010 ; Lawrence et al, 2011 ; Staebler et al, 2011b ; Renneberg et al, 2012 ; Dixon-Gordon et al, 2013 ; Chapman et al, 2014 , 2015 ; Gutz et al, 2015 , 2016 ; Ernst et al, 2017 ; Savage and Lenzenweger, 2017 ). Some of these studies revealed that feelings of exclusion in BPD were evoked similarly in the exclusion and in the inclusion condition ( Staebler et al, 2011a ; Renneberg et al, 2012 ; Domsalla et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Algunos autores proponen que las personas con trastorno límite de la personalidad tienden a tener un déficit en la conciencia emocional y evitar las emociones desagradables, por lo que es posible que no puedan representar con precisión estos sentimientos en una medida interna. En estudios donde se encontraron resultados negativos para la expresión neutra, los resultados son ampliamente consistentes con la hipótesis de que los participantes con trastorno límite de la personalidad pueden no ser capaces de representar con precisión sus sentimientos y pueden poseer menos autoconciencia (Savage & Lenzenweger, 2018).…”
Section: Discussionunclassified
“…We offer our model as a heuristic and substantive explanation of the underlying nature of both personality and personality disturbance. We believe it suggests an integrated basis for understanding both personality and personality disturbance while simultaneously suggesting important vectors for empirical research across levels of analysis, ranging from the genetic and epigenetic [see 7 for extensive discussion of genetic and epigenetic considerations], through neurobiology, to neurocognitive processes [36] and phenotypic individual differences, all the while allowing for interpersonal [37] and environmental inputs.…”
Section: Conceptual Overview Of a Neurobehavioral Model Underpinning mentioning
confidence: 99%